Regional dimensions of Turkish foreign policy - ابراهيم شادي; حسين طلال مقلد (Latakia University Journal - Economic and Legal Sciences Series, 2024)
This research seeks to provide an analytical vision of the Turkish role in the region, considering Turkey a model of power A rising society seeking to gain a major regional position in light of major changing international events. This research aims to study the development in Turkish foreign policy and provide an analytical vision of the Turkish regional role in the region, in addition to studying the regional dimension of Turkish foreign policy. The researcher reached results and recommendations, the most important of which are: Turkey has adopted a proactive policy regarding all regional issues by activating its smart power. Regional and international interactions also have an important role in opening the way for Turkish engagement in its new form within the region, including crises and wars, the necessity of strengthening regional cooperation institutions, At the regional level, to ensure the greatest amount of common interests are achieved, and to enhance the levels of mutual dependence between the countries of the region, in order to achieve the greatest degree of peaceful cooperation and keep the region away from crises and wars.